A escrita acadêmica nas vivências escolares: potencialidades e dificuldade - Nery, Jaqueline Lima da Silva (2022)
In the academic field, many students, when producing a text, identify their criteria as a situation that hinders and restricts their writing process. In this process, students mobilize their repertoire, experiences and interests to develop authentic and, at the same time, legitimate textual expression in the academy. However, they are faced with criteria and requirements that prescind the subject who writes (student), don't negotiate with him and, often, without proper means of access and learning conditions, inhibits writing activity. The perception of the problem as an individual issue enforces the attribution of the problem to the subject, in a meritocratic perspective, and as an expression of academic failure. This work aimed to contribute to the understanding of this process, having as a horizon to recognize and legitimize the complex process of meaning creation for students on academic writing, subsidize and strengthen intervention actions at the individual and collective scopes, based on socio-historical psychology, based on the assumption of that the process of human constitution takes place through mediations, social situations of development that can affect students as conditions that restrict or emancipate them. This research had three master's students from an HEI in São Paulo and the meeting took place online due to the situation of the COVID-19 pandemic. The focus of the investigation was to privilege as a procedure the listening in a conversation circle of the experiences in the schooling process with the objective of researching the relationship between academic trajectory and self-perception of writing ability in graduate students. A comprehensive analysis of the data was carried out based on the theoreticalmethodological assumptions and categories of historical-dialectical materialism and socio-historical psychology. The study points out medicalizing experiences producing suffering and situations of exclusion. Elaborations made by the subjects in the face of the identification of problems, difficulties, anxieties, stories and hopes in common stand out. This research shows that, in collective settings, students welcome difference and, when telling their story aloud, or listening to a story that belongs to a colleague, but which brings fragments of something that brings them together, they engage in seeking possibilities of overcoming difficulties, constituting new meanings for their school history and the production of a powerful and scientific writing. We emphasize the need to broaden the discussion and implementation of educational activities that aim to recognize and legitimize the complex process of production of academic writing, subsidizing and strengthening intervention actions at the individual and collective levels